COVID-19 infection in severe Alpha 1-antitrypsin deficiency: Looking for a rationale. (July 2021) - Ferrarotti, I.; Ottaviani, S.; Balderacchi, A.M.; Barzon, V.; De Silvestri, A.; Piloni, D.; Mariani, F.; Corsico, A.G.
Abstract: The clinical manifestations of COVID-19 are heterogeneous: 46.4% of patients admitted into hospital reported to have at least one comorbidity. Comorbidities such as COPD, diabetes, hypertension and malignancy predispose patients with Covid-19 to adverse clinical outcomes. Alpha 1-antitrypsin deficiency (AATD) is a genetic disorder caused by pathological mutation(s) in the SERPINA1 gene resulting in an imbalance in proteinase activity which may lead to premature emphysema and COPD. Our aim was to investigate whether people with severe AAT deficiency (AATD) have an increased risk of (severe) COVID-19 infection. We collected data on COVID-19 symptoms, laboratory-confirmed infection, hospitalization and treatment by means of a telephone survey, directly administered to Italian severe AATD subjects in May 2020. We then compared our findings with data collected by the Istituto Superiore di Sanità on the total population in Italy during the same period. We found an higher frequency of SARS-CoV-2 infection in our cohort (3.8%) compared to national data regarding infection, thus giving severe AATD a relative risk of 8. 8 (95%CI 5.1-20, 0; p<0.0001) for symptomatic SARS-CoV-2 infection. Moreover, the relative risk (RR) was higher in AATD patients with pre-existing lung diseases (RR 13.9; 95%CI 8.0-33.6; p<0.001), but with a similar death rate (1 in 8, 12.5%) compared to the general population (13.9%; RR 0.9). These preliminary findings highlight the importance of close surveillance in the spread of COVID-19 in patients with severe AATD and underlines the need for further studies into the role of the antiprotease shield in preventing SARS-Cov-2 infection. Highlights: Alpha 1-antitrypsin (AAT) is the most abundant serum proteinase. AAT has a significant anti-inflammatory role with immunomodulatory properties. SARS-CoV-2 infection has high incidence in subjects with severe AAT deficiency. AAT severe deficiency has a relative risk of 8, 8 for SARS-CoV-2 infection.